Evaluation and management of hand, wrist and elbow injuries in ice hockey - Tedesco, L. J.; Swindell, H. W.; Anderson, F. L.; Jang, E.; Wong, T. T.; Kazam, J. K.; Kadiyala, R. K.; Popkin, C. A. (Open Access Journal of Sports Medicine, 2020)
Ice hockey continues to be a popular, fast-paced, contact sport enjoyed internationally. Due to the physicality of the game, players are at a higher risk of injury. In the 2010 Winter Olympics, men`s ice hockey had the highest injury rate compared to any other sport. In this review, we present a comprehensive analysis of evaluation and management strategies of common hand, wrist, and elbow injuries in ice hockey players. Future reseach focusing on the incidence and outcomes of these hand, wrist and elbow injuries in ice hockey players is warranted.